1996
DOI: 10.1128/aac.40.8.1846
|View full text |Cite
|
Sign up to set email alerts
|

4-aminoquinoline analogs of chloroquine with shortened side chains retain activity against chloroquine-resistant Plasmodium falciparum

Abstract: We have synthesized several 4-aminoquinolines with shortened side chains that retain activity against chloroquine-resistant isolates of Plasmodium falciparum malaria (W. Hofheinz, C. Jaquet, and S. Jolidon, European patent 94116281.0, June 1995). We report here an assessment of the activities of four selected compounds containing ethyl, propyl, and isopropyl side chains. Reasonable in vitro activity (50% inhibitory concentration, < 100 nM) against chloroquine-resistant P. falciparum strains was consistently… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
119
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 216 publications
(128 citation statements)
references
References 26 publications
9
119
0
Order By: Relevance
“…Nevertheless, FQ shares some CQ structural characters (7-chloroquinoline functionality, length of the side chain) which are optimal for antimalarial ecacy (Biot et al 1999a;O'Neill et al 1998). It is already known that many quinoline derivatives are capable of overcoming chloroquine resistance (De et al 1998;Kotecka et al 1997;Ridley et al 1996), although some level of cross-resistance may be involved (Ridley et al 1996). So far, no cross-resistance has been observed between FQ and chloroquine (Domarle et al 1998).…”
Section: Discussionmentioning
confidence: 96%
“…Nevertheless, FQ shares some CQ structural characters (7-chloroquinoline functionality, length of the side chain) which are optimal for antimalarial ecacy (Biot et al 1999a;O'Neill et al 1998). It is already known that many quinoline derivatives are capable of overcoming chloroquine resistance (De et al 1998;Kotecka et al 1997;Ridley et al 1996), although some level of cross-resistance may be involved (Ridley et al 1996). So far, no cross-resistance has been observed between FQ and chloroquine (Domarle et al 1998).…”
Section: Discussionmentioning
confidence: 96%
“…Furthermore, when the Cl atom was substituted by H-atom, no marked difference in antimalarial activity (ITG2G1 strain) was observed. In spite of resistance to CQ, previous works (both computational and experimental) have shown that modification of the lateral side chain of CQ results in aminoquinoline derivatives that avoid the CQ resistance mechanism [98][99][100][101]. Aguiar et al [102] compared the antimalarial activity mono (39a) and bisquinoline (39b) derivative of CQ against P. falciparum in-vitro and P. berghei in-vivo (Figure 29).…”
Section: Q-l-gmentioning
confidence: 95%
“…4-Aminopyridine substructure of 4-aminoquinoline also helped in binding with the heme [91]. The presence of linker alkyl chain between triazine and quinoline nucleus is essential, but both shortening (2-3 carbon atoms) and lengthening (10-12 carbon atoms) of the alkyl chain led to compounds with retained antimalarial activity [92,93]. Substitution of diethyl group by metabolically stable side chain of tert-butyl group as well as the heterocyclic functionality such as morpholinyl, piperidinyl or pyrrolidinyl groups led to increase in antimalarial activity [94].…”
Section: Antimalarial Activitymentioning
confidence: 96%